2021
DOI: 10.3389/fendo.2021.727229
|View full text |Cite
|
Sign up to set email alerts
|

Does the Anti-Mullerian Hormone Decline Rate Improve the Prediction of Age at Menopause?

Abstract: ObjectivesThere are controversial studies investigating whether multiple anti-Mullerian hormone (AMH) measurements can improve the individualized prediction of age at menopause in the general population. This study aimed to reexplore the additive role of the AMH decline rate in single AMH measurement for improving the prediction of age at physiological menopause, based on two common statistical models for analysis of time-to-event data, including time-dependent Cox regression and Cox proportional-hazards regre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 41 publications
0
21
0
Order By: Relevance
“…Similarly, in the TLGS cohort, the serum AMH trajectory was a strong predictor for age at menopause ( Gohari et al , 2016 ), with subsequent analyses demonstrating that the addition of the AMH annual decline within models significantly improved the prediction of age at menopause over AMH and age alone ( Ramezani Tehrani et al , 2020 ). Analysis of that study using Cox proportional hazards showed that repeated measurement of AMH only slightly improved prediction of age at menopause; the best model for predicting menopause only generated a 3% improvement in prediction, with the C -statistic increasing from 0.71 (95% CI: 0.69–0.73) at baseline to 0.74 (95% CI: 0.71–0.76) when a second measurement and calculation of the annual decline were included ( Ramezani Tehrani et al , 2021 ). These contradictory results may be partly due to the different modelling used, the variation in time to menopause, the different time periods between repeat AMH measures, and/or the heterogeneity in populations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, in the TLGS cohort, the serum AMH trajectory was a strong predictor for age at menopause ( Gohari et al , 2016 ), with subsequent analyses demonstrating that the addition of the AMH annual decline within models significantly improved the prediction of age at menopause over AMH and age alone ( Ramezani Tehrani et al , 2020 ). Analysis of that study using Cox proportional hazards showed that repeated measurement of AMH only slightly improved prediction of age at menopause; the best model for predicting menopause only generated a 3% improvement in prediction, with the C -statistic increasing from 0.71 (95% CI: 0.69–0.73) at baseline to 0.74 (95% CI: 0.71–0.76) when a second measurement and calculation of the annual decline were included ( Ramezani Tehrani et al , 2021 ). These contradictory results may be partly due to the different modelling used, the variation in time to menopause, the different time periods between repeat AMH measures, and/or the heterogeneity in populations.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies assessed the utility of repeat AMH measures, incorporating a variety of different mathematical approaches to try to model the menopausal transition or improve the prediction of time to menopause compared with single measurements. These included differences in absolute values ( Iino et al , 2013 ), Weibull accelerated failure time models ( Tehrani et al , 2013 ), flexible parametric survival models ( Tehrani et al , 2013 ; Ramezani Tehrani et al , 2016 ), mixed models ( de Kat et al , 2016 ), Kaplan–Meier estimations ( Freeman et al , 2012a ), and Cox proportional hazards models with time-varying covariates ( de Kat et al , 2019 ; Ramezani Tehrani et al , 2021 ). The findings are inconsistent.…”
Section: Resultsmentioning
confidence: 99%
“…To address this issue, ultrasensitive assays and longitudinal measurements over time may be helpful. Tehrani et al demonstrated better predictive potential using the log annual AMH levels decline rate than using AMH levels at a fixed point (C‐static:0.64 in AMH levels and 0.84 in log annual AMH levels decline rate) 24 . The sensitivity and positive predictive value for predicting the final menstrual period were higher using a cut‐off of AMH levels as <10 pg/mL than <100 pg/mL 25 …”
Section: Resultsmentioning
confidence: 99%
“…They described that the rate of AMH decline has a low discriminative ability to estimate the risk of early menopause [ 42 ]. Conversely, an analysis of the Tehran Lipid and Glucose Study population showed that the rate of AMH decline is the most effective predictor of early menopause [ 43 ]. They demonstrated that a 1-unit increase in the yearly AMH decline rate was associated with a 10.8-times higher risk of early menopause [ 43 ].…”
Section: Discussionmentioning
confidence: 99%